The Influence of Hedonic Shopping Motivation and Self-Control on the Impulsive Buying Tendency - Aurelia Ardhani Nathania; Andi Supandi Suaid Koentary (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2026)
The increasing trend of Shopee PayLater usage, particularly among college students who do not have an income, warrants attention as many use it for recreational purposes without sufficient self-control, thus increasing the tendency for impulsive buying that can lead to uncontrolled financial burdens. This study has a hypothesis that hedonic shopping motivation and self-control have a significant influence on impulsive purchasing tendencies among Shopee PayLater users. The participants consisted of 141 college students aged 18–25 who actively use SPayLater. Multiple regression analysis showed that both hedonic shopping motivation (β = .20, 95% CI [.09, .31]) and self-control (β = -.57, 95% CI [-.68, -.44]) significantly influence impulsive buying tendency. The higher the hedonic motivation and the lower the self-control, the higher the tendency for impulsive buying (Impulsive Buying Tendency = 4.41 + .20 (Hedonic Motivation) – .57 (Self-Control). This study contributes to consumer psychology literature regarding the use of pay later services and provides insights to the public on the importance of managing emotional impulses and enhancing self-control.